Video-based agricultural extension - integration of videos to create awareness among farmers as part of an extension approach - CGIAR Research Program on Policies, Institutions, and Markets (2017)
Initial study in Ethiopia with Digital Green and Ministry of Agriculture found positive effects from the video mediated extension approach that has encouraged the implementation partners to continue their use of the innovation.